Canadian Foreign Policy: An Exploration of Israel and Canada as "Best Friends" - Tayyem, Sarah (Université d'Ottawa | University of Ottawa, 2014)
In 2012, Foreign Affairs Minister John Baird stated that Israel has “no better friend” than Canada. And indeed, an analysis of the voting records of Canada at the United Nations Commission on Human Rights, Human Rights Council, Security Council, and the General Assembly reveals a clear political bias in the voting of the Stephen Harper government towards Israel, a bias that isolates Canada from most of the international community. Not only is Canada supportive of Israel, but a review of Canada’s political and economic relationship with Israel shows that the current relationship is much closer than that of between previous governments. This shift can be explained in part by this current government’s ideological support for Israel, in part by their aspiration to make economic conservatism central to Canadian foreign policy, and, as an aspect of their strategy to appeal to the Conservative voter base. This support for Israel is further reinforced through the secondary factors of a disinterested Canadian public, an underlying orientalist power structure, and the influence of the pro-Israeli lobby. Canada’s new closeness with Israel is not likely to have any long-lasting implications for Canada’s role in the Israel-Palestinian conflict; however, it has likely decreased Canadian influence in the Middle East and contributed to a broader Canadian-led cooling of relationships with the international community.